Cellulose dispersion resin composition, fiber material, and molding material

JP7643645B2Active Publication Date: 2025-03-11DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024531103
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-06
Filing Date
2023-11-02
Publication Date
2025-03-11
Estimated Expiration
2043-11-02

AI Technical Summary

Benefits of technology

【0008】 本発明のセルロース分散用樹脂組成物は、セルロースの分散性に優れることから、ポリエチレン等のマトリックス樹脂とセルロース繊維とからなる成形品の機械的強度を効果的に補強することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643645000001
    Figure 0007643645000001
Patent Text Reader

Abstract

Provided is a resin composition for cellulose dispersion containing an acrylic resin (A) that has as essential raw materials an alkyl (meth)acrylate (a1) having a C4 or more alkyl group, one or more unsaturated monomers (a2) selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and a (meth)acrylamide (a3) having an amide group other than the unsaturated monomer (a2), wherein the resin composition for cellulose dispersion is characterized in that, in the monomer components that are the raw materials of the acrylic resin (A), the alkyl (meth)acrylate (a1) is 20-50 mass%, the unsaturated monomer (a2) is 10-50 mass%, and the (meth)acrylamide (a3) is 30-70 mass%. Due to its excellent dispersibility of cellulose, this resin composition for cellulose dispersion can effectively reinforce the mechanical strength of molded articles comprising cellulose fibers and a matrix resin such as polyethylene.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for dispersing cellulose, a fiber material, and a molding material. [Background technology]

[0002] Cellulose nanofibers are natural nanofillers derived from plants, and as biomass fibers, they have been attracting attention for use in fiber-reinforced composite materials. As composite materials using such cellulose nanofibers, fiber-reinforced composite materials have been proposed that contain cellulose fibers in a matrix material, and the surfaces of the cellulose fibers are graft-modified by graft polymerization of a polymerizable component in an aqueous system (see, for example, Patent Document 1).

[0003] However, because the graft component of this composite material has high polarity, when a low-polarity matrix material such as polyolefin is used, the cellulose fibers are insufficiently dispersed in the matrix material, and the mechanical properties of the molded product are not fully expressed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-67817 A Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a cellulose dispersion resin composition, a fiber material, and a molding material which contain cellulose fibers and can give molded articles having excellent mechanical strength. [Means for solving the problem]

[0006] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a resin composition for dispersing cellulose, which contains a specific acrylic resin whose essential raw materials are an alkyl (meth)acrylate having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide, can give molded products which have excellent cellulose dispersibility, a high biomass content, and excellent mechanical strength, and have thus completed the present invention.

[0007] That is, the present invention relates to a resin composition for dispersing cellulose, which contains an acrylic resin (A) having, as essential raw materials, an alkyl (meth)acrylate (a1) having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3), wherein the content of the alkyl (meth)acrylate (a1) in the monomer components serving as raw materials for the acrylic resin (A) is 20 to 50 mass%, the content of the unsaturated monomer (a2) is 10 to 50 mass%, and the content of the (meth)acrylamide (a3) ​​is 30 to 70 mass%. Effect of the Invention

[0008] Since the resin composition for dispersing cellulose of the present invention has excellent dispersibility of cellulose, it can effectively reinforce the mechanical strength of a molded article made of a matrix resin such as polyethylene and cellulose fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The resin composition for cellulose dispersion of the present invention is a resin composition for cellulose dispersion containing an acrylic resin (A) whose essential raw materials are an alkyl (meth)acrylate (a1) having an alkyl group having 4 or more carbon atoms, one or more unsaturated monomers (a2) selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3), in which the alkyl (meth)acrylate (a1) accounts for 20 to 50 mass%, the unsaturated monomer (a2) accounts for 10 to 50 mass%, and the (meth)acrylamide (a3) ​​accounts for 30 to 70 mass% in the monomer components that are raw materials for the acrylic resin (A).

[0010] In the present invention, the term "(meth)acrylate" refers to either or both of "acrylate" and "methacrylate", the term "(meth)acrylamide" refers to either or both of "acrylamide" and "methacrylamide", and the term "(meth)acrylic acid" refers to either or both of "acrylic acid" and "methacrylic acid". In addition, the alkyl group in the present invention includes a cycloalkyl group.

[0011] The alkyl (meth)acrylate (a1) has an alkyl group having 4 or more carbon atoms, and by using this, cellulose dispersibility is excellent even in a matrix material with low polarity. Examples of the alkyl (meth)acrylate (a1) include n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and stearyl (meth)acrylate. Among these, alkyl (meth)acrylates having an alkyl group having 4 to 18 carbon atoms are preferred because they have excellent cellulose dispersibility and further improve the mechanical strength of the molded product. These alkyl (meth)acrylates (a1) can be used alone or in combination of two or more kinds.

[0012] The unsaturated monomer (a2) is one or more monomers selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and can be used to react with cellulose. Examples of the unsaturated dibasic acid include (anhydrous) maleic acid, fumaric acid, (anhydrous) itaconic acid, etc. These unsaturated dibasic acids can be used alone or in combination of two or more.

[0013] The unsaturated monomer having a keto group may be, for example, diacetone (meth)acrylamide. The unsaturated monomer having a keto group may be used alone or in combination of two or more kinds.

[0014] The (meth)acrylamides (a3) ​​can be used alone or in combination of two or more kinds.

[0015] As raw materials for the acrylic resin (A), in addition to the alkyl (meth)acrylate (a1), the unsaturated monomer (a2), and the (meth)acrylamide (a3), other monomers (a4) can be used as necessary.

[0016] Examples of the other monomer (a4) include (meth)acrylic acid, 2-methylaminoethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, γ-methacryloxypropyl trimethoxysilane, vinyltriethoxysilane, glycidyl (meth)acrylate, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-dodecylacrylamide, N-propoxymethylacrylamide, 6-(meth)acrylamide, 1,2-dimethyl ( ... Examples of the (meth)acrylates having functional groups such as acrylamidohexanoic acid, (meth)acryloylmorpholine, N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, and N-[2,2-dimethyl-3-(dimethylamino)propyl]acrylamide include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isobornyl (meth)acrylate, benzyl (meth)acrylate, diethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerin di(meth)acrylate, styrene, α-methylstyrene, paramethylstyrene, and chloromethylstyrene. These other monomers (a4) can be used alone or in combination of two or more.

[0017] The amount of the alkyl (meth)acrylate (a1) used is 20 to 50 mass% in the monomer component that is the raw material of the acrylic resin (A), and is preferably 25 to 40 mass% because this further improves the cellulose dispersibility and the mechanical strength of the resulting molded product.

[0018] The amount of the unsaturated monomer (a2) used is 10 to 50 mass% in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 10 to 40 mass% because this further improves the cellulose dispersibility and the mechanical strength of the resulting molded product.

[0019] The amount of the (meth)acrylamide (a3) ​​used is 30 to 70 mass% in the monomer component that is the raw material of the acrylic resin (A), and is preferably 35 to 60 mass% because this further improves the cellulose dispersibility and the mechanical strength of the resulting molded product.

[0020] The weight-average molecular weight of the acrylic resin (A) is preferably 10,000 to 100,000, since this improves the cellulose dispersibility and the mechanical strength of the resulting molded article. Here, the weight-average molecular weight is a value calculated in terms of polystyrene based on gel permeation chromatography (hereinafter abbreviated as "GPC") measurement.

[0021] The acrylic resin (A) can be produced, for example, by radical polymerization of the alkyl (meth)acrylate (a1), the unsaturated monomer (a2), and the (meth)acrylamide (a3), and, if necessary, other monomers (a4), in an organic solvent and / or water in the presence of a polymerization initiator at a temperature of 60 to 140°C.

[0022] Examples of the organic solvent that can be used include aromatic solvents such as toluene and xylene, alicyclic solvents such as cyclohexanone, ester solvents such as butyl acetate and ethyl acetate, alcohol solvents such as ethanol, isobutanol, normal butanol, and isopropyl alcohol, cellosolve solvents such as sorbitol and propylene glycol monomethyl ether acetate, and ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone. These solvents can be used alone or in combination of two or more.

[0023] Examples of the polymerization initiator include azo compounds such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), and azobiscyanovaleric acid; organic peroxides such as tert-butyl peroxypivalate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, di-tert-butyl hydroperoxide, cumene hydroperoxide, benzoyl peroxide, and tert-butyl hydroperoxide; and inorganic peroxides such as hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate. These polymerization initiators can be used alone or in combination of two or more kinds. The polymerization initiator is preferably used in an amount of 0.1 to 10% by mass based on the total amount of monomers that are raw materials for the acrylic resin (A).

[0024] The resin composition for cellulose dispersion of the present invention contains the acrylic resin (A). If necessary, the resin composition may further contain polyethylene-based resins (PE) such as high density polyethylene (HDPE), low density polyethylene (LDPE), and biopolyethylene, polypropylene-based resins (PP), olefin-based resins such as vinyl chloride resins, styrene resins, (meth)acrylic resins, and vinyl ether resins, nylon resins, polyamide-based resins, polycarbonate-based resins, polysulfone-based resins, polyester-based resins, cellulose-based resins such as triacetylated cellulose and diacetylated cellulose, and polyamide-based resins such as polyamide 6 (PA6, ε- Thermoplastic resins such as polyamide 66 (PA66, polyhexamethylene adipamide), polyamide 11 (PA11, a polyamide obtained by ring-opening polycondensation of undecane lactam), polyamide 12 (PA12, a polyamide obtained by ring-opening polycondensation of lauryl lactam), compatibilizers, surfactants, starches, polysaccharides such as alginic acid, natural proteins such as gelatin, glue, and casein, inorganic compounds such as tannins, zeolites, ceramics, and metal powders, colorants, plasticizers, fragrances, pigments, flow regulators, leveling agents, conductive agents, antistatic agents, UV absorbers, UV dispersants, and deodorants can also be used in combination.

[0025] The fiber material of the present invention contains the cellulose dispersion resin composition and cellulose fibers, and the cellulose fibers are surface-treated with the cellulose dispersion resin composition, thereby achieving excellent dispersibility of the cellulose fibers in the matrix resin.

[0026] The cellulose fibers are preferably cellulose nanofibers (hereinafter sometimes abbreviated as "CNF"), since this further improves the mechanical strength of the resulting molded article.

[0027] The fiber material can be easily obtained, for example, by subjecting the monomers that are the raw materials of the acrylic resin (A) to the above-mentioned radical polymerization in the presence of CNF.

[0028] The fiber material can be dried, for example, by a drum dryer, a disk dryer, a conical dryer, a spray dryer, thin film distillation or the like, and then pulverized into fine particles by a Henschel mixer or the like, and used as a molding material.

[0029] The molding material of the present invention contains the above-mentioned fiber material and a thermoplastic resin as a matrix resin. Examples of the thermoplastic resin include polyolefin resin, polycarbonate resin, polyamide resin, polyester resin, epoxy resin, etc., and among these, polyolefin resin is preferred, and polyethylene is more preferred.

[0030] The molding material of the present invention can be obtained by kneading the above-mentioned fiber material and a thermoplastic resin by a known kneading method.

[0031] The molding material of the present invention can be used to produce molded articles having excellent mechanical strength, and therefore can be used to produce various molded articles. EXAMPLES

[0032] The present invention will now be described more specifically with reference to examples and comparative examples.

[0033] Example 1 In a 2.0L reaction vessel equipped with a stirrer, a thermometer, a cooler, and a nitrogen blower, 700.0 parts by mass of CNF water dispersion (Sugino Machine's "Binfi-S FMa-10010", solid content 10.0 mass%) and 700.0 parts by mass of isopropyl alcohol were charged and heated to 70 ° C., and then a mixture of 38.0 parts by mass of acrylamide, 21.0 parts by mass of lauryl methacrylate, 11.0 parts by mass of maleic acid, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion-exchanged water was dropped over 1.5 hours. After 3 hours had passed since the end of the dropwise addition, the mixture was cooled. The non-volatile content of the obtained fiber material (1) was 8.5 mass%, and the viscosity at 25 ° C was 265 mPa s.

[0034] Example 2 In a 2.0L reaction vessel equipped with a stirrer, thermometer, cooler, and nitrogen blower, 700.0 parts by mass of CNF water dispersion (Sugino Machine's "Binfi-S FMa-10010", solid content 10.0 wt%) and 700.0 parts by mass of isopropyl alcohol were charged and heated to 70 ° C., and then a mixture of 28.0 parts by mass of acrylamide, 21.0 parts by mass of lauryl methacrylate, 21.0 parts by mass of diacetone acrylamide, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion-exchanged water was dropped over 1.5 hours. After 3 hours had passed since the end of the dropwise addition, the mixture was cooled. The non-volatile content of the obtained fiber material (2) was 8.7% by mass, and the viscosity at 25 ° C was 247 mPa s.

[0035] Example 3 In a 2.0L reaction vessel equipped with a stirrer, thermometer, cooler, and nitrogen blower, 700.0 parts by mass of CNF water dispersion (Sugino Machine's "Binfi-S FMa-10010", solid content 10.0 wt%) and 700.0 parts by mass of isopropyl alcohol were charged and heated to 70°C, and then a mixture of 28.0 parts by mass of acrylamide, 21.0 parts by mass of butyl acrylate, 21.0 parts by mass of diacetone acrylamide, 70.0 parts by mass of isopropyl alcohol, 0.5 parts by mass of ammonium persulfate, and 70.0 parts by mass of ion-exchanged water was dropped over 1.5 hours. After 3 hours had passed since the end of the dropwise addition, the mixture was cooled. The non-volatile content of the obtained fiber material (3) was 8.5% by mass, and the viscosity at 25°C was 196 mPa·s.

[0036] Comparative Example 1 A 2.0 L reaction vessel equipped with a stirrer, thermometer, cooler, and nitrogen blower was charged with 700.0 parts by mass of a CNF water dispersion (Sugino Machine's "Binfi-S FMa-10010", solids content 10.0 wt%) and 840.0 parts by mass of ion-exchanged water, to which 2.1 parts by mass of diammonium cerium (IV) nitrate and 70 parts by mass of methyl methacrylate were added and reacted at a temperature of 30°C for 4 hours. The non-volatile content of the obtained fiber material (R1) was 8.6% by mass, and the viscosity at 25°C was 231 mPa s.

[0037] Comparative Example 2 As the fiber material (R2), a CNF water dispersion ("Binfi-S FMa-10010" manufactured by Sugino Machine, solid content 10.0% by mass) was used.

[0038] [Manufacturing of molding materials and molded products] The fiber material obtained above was dried with a disk dryer, and the dried-up product was mixed with polyethylene powder ("SHC7260" manufactured by Braskem) as a matrix resin so that the CNF content was 5% by mass. The resulting mixture was melt-kneaded for 10 minutes at 140°C and 200 rpm in a small kneading device ("DSM Xplore1 15" manufactured by Leo Labs, Inc.). The resulting molding material was injection-molded using a small injection molding machine (manufactured by Leo Labs, Inc.) at a mold temperature of 50°C and a cylinder temperature of 150°C to produce a molded product (74 mm long, 5 mm wide, 2 mm thick) for a tensile test.

[0039] [Evaluation of mechanical strength of molded products] The tensile strength and tensile modulus of the obtained tensile test specimens were measured using a tensile testing machine ("AUTOGRAPH AGS-X" manufactured by Shimadzu Corporation) under conditions of a tensile speed of 50 mm / min, a chuck distance of 50 mm, a temperature of 23°C, and a humidity of 50%.

[0040] The monomer composition of the acrylic resin (A) used in Examples 1 to 3 and Comparative Examples 1 and 2, and the evaluation results are shown in Table 1.

[0041] [Table 1]

[0042] It was confirmed that the molded articles obtained using the resin compositions for cellulose dispersion of the present invention in Examples 1 to 3 had excellent mechanical strength.

[0043] On the other hand, in Comparative Example 1, which is an example in which methyl methacrylate was used as the raw material of the acrylic resin, it was confirmed that the tensile modulus of elasticity of the molded product was insufficient.

[0044] Comparative Example 2 is an example in which CNF that was not treated with acrylic resin was used, and it was confirmed that the tensile modulus of elasticity of the molded article was insufficient.

Claims

1. The resin composition for cellulose dispersion contains an acrylic resin (A) whose essential raw materials are an alkyl (meth)acrylate (a1) having an alkyl group having 4 to 18 carbon atoms, one or more unsaturated monomers (a2) selected from the group consisting of unsaturated dibasic acids and unsaturated monomers having a keto group, and (meth)acrylamide (a3), wherein the monomer components that are the raw materials for the acrylic resin (A) contain 20 to 50% by mass of the alkyl (meth)acrylate (a1), 10 to 50% by mass of the unsaturated monomer (a2), and 30 to 70% by mass of the (meth)acrylamide (a3).

2. A fiber material comprising the resin composition for dispersing cellulose according to claim 1 and cellulose fibers.

3. A molding material comprising the fiber material according to claim 2 and a thermoplastic resin.

Citation Information

Patent Citations

  • Fiber-reinforced composite material and method for producing the same

    JP2009067817A

  • Composition containing cellulose and dispersant

    JP2014162880A

  • Manufacturing method of resin composition, and manufacturing method of molded body using the resin composition

    JP2019189758A

  • Low viscosity, fast curing binder for cellulose

    US5278222A